Intranasal Fentanyl for Procedural Analgesia in Preterm Infants - Cheng, Charles; Tabbara, Najla; Cheng, Carol; Shah, Vibhuti (Frontiers in Pain Research, 2022)
Background Despite the availability of evidence-based analgesic strategies, neonatal pain management continues to be suboptimal. Intranasal (IN) fentanyl is an alternative pharmacotherapy for procedural pain in neonatal units. The objective was to evaluate the effectiveness and safety of IN fentanyl for procedural pain in preterm infants. Methods A retrospective cohort study was conducted in infants who received IN fentanyl between May 2019 and December 2020 at an academic neonatal intensive care unit. Main outcome measures were pain responses, physiological parameters before and up to 60 min after IN fentanyl administration, and adverse events. Paired t-test and analysis of variance were used to compare pain scores and physiological parameters, respectively. Results Thirteen infants received IN fentanyl on 22 occasions. Median (interquartile range [IQR]) gestational age and birthweight were 27 (25, 27.6) weeks and 850 (530, 1,030) grams, while median (IQR) post-menstrual age and weight were 30.9 (28.9, 32.9) weeks and 1,280 (945, 1,623) grams at the time of IN fentanyl administration. IN fentanyl was most used for lumbar puncture (55%) followed by insertion of epicutaneo-caval catheters (27%). There was a difference between the mean pre- and post-procedure Premature Infant Pain Profile scores of 1.3 (95% CI = 0.07, 2.5; p = 0.04). Physiological parameters did not differ before and up to 60 min post IN fentanyl administration (p > 0.05). Two adverse events (one apnea and one desaturation) were noted. Conclusion In our limited experience, IN fentanyl appears to be an alternative pharmacotherapy for procedural pain management in the absence of intravenous access in preterm infants.